‘’STUDY OF C-REACTIVE PROTEIN IN VARIOUS MENINGITIS PATIENTS’’ - Dr. Ravi Agrawal; Dr. Pradeep Kumar kori (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: Meningitis is a clinical syndrome characterized by inflammation of meninges. The classic triad of meningitis consists of fever, headache and neck stiffness. Pneumococcal meningitis is the most common bacterial cause of meningitis. Most patients recover completely if appropriate antibiotic therapy is instituted promptly. Tubercular meningitis is a very critical disease in terms of fatal outcome and permanent sequelae, requiring rapid diagnosis and treatment. Death may occur as a result of missed diagnosis and delayed treatment. Enterovirus is the most common cause of viral meningitis. Cryptococcal meningitis may be seen especially in persons with defective cell mediated immunity. Encephalitis primarily involves the brain; it often involves the meninges as well (meningoencephalitis). This study is done to emphasize the importance of early diagnosis, so that prompt management is given at appropriate time.Aim: This is a prospective observational, single center study done in Department of medicine NSCB medical college hospital Jabalpur in 93 patients of acute meningoencephalitis cases:  1st March.2020 to 31 August 2021. The main aim of this study is ‘To study serum c-reactive protein levels in differentiating bacterial meningitis from viral meningitis’’Materials And Methods: In the present study, we recruited 93 patients who presented with meningitis and meningoencephalitis who fulfilled the inclusion criteria. Proforma is used to collect data needed. Data are statistically analysed.Results: in this study, most of the patients were males and young adults. Surprisingly, tuberculous meningitis was the most common overall cause in our study. Tuberculous meningitis was the most common cause in patient with subacute meningitis. All patients with chronic presentation had tuberculous meningitis. We came across atypical presentation of cryptococcal meningitis in a non-HIV patient. 47 patients recovered well without neurological deficits.  Both viral meningo-encephalitis and pyogenic meningitis constituted most of the cases of acute the common initial presenting symptoms were fever (89%) and Vomiting (89%) >altered sensorium> headache and neck pain and stiffness>Focal neurological deficit> seizure. Fever was the most common initial presenting symptom. 86 patients (92.5%) had fever and headache (92.5%). 31 patient was found as bacterial meningitis which had s-crp value mostly ranging between >24 mg/l, out of them 19 patient had s-crp value >48 mg/l (61.29%). Most of them had poor prognosis and presented with altered sensorium and high-grade fever. most of the case out of 37 had s-crp value between intermediate range (12-48) mg/l and 2 patients had range between >48 mg/l which had miliary tuberculosis.Conclusion: Estimation of C-reactive protein in serum is the cheapest, sensitive and specific test to differentiate bacterial from viral infections. It is a simple qualitative as well as quantitative test and can be done as a bed side investigation. With serum C-reactive protein, a definite etiological diagnosis can be made rapidly at the time of admission itself.